(untitled) (Research, Society and Development, 2022)
Low back pain is defined as pain or discomfort located below the ribs and above the gluteal region, being one of the most frequent musculoskeletal complaints in the world. Normally, the standard treatment includes physical therapy and prescription of medications such as simple analgesics, opioids, and non-steroidal anti-inflammatory drugs (NSAIDs), however, other techniques have shown remarkable results, such as auriculotherapy, which may be an option for pain relief. low back. Objective: To analyze the effectiveness of Chinese auriculotherapy in low back pain. Method: A literature review of the literature was carried out, with a search for articles available in English and Portuguese in the last 15 years. The articles were selected from the scientific databases Scientific Electronic Library Online (Scielo) and Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed. Results: The results obtained in this study showed that treatment through auriculotherapy is effective and minimally invasive, is a simple way to provide pain relief. Conclusion: Auriculotherapy showed significant results for the relief of low back pain. However, more studies are needed to determine the effectiveness of auriculotherapy.